Development of stratospheric communication platforms (SCP) as backbone to terrestrial networks - Dimov Stojce Ilcev (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper are introduced the new airship techniques and technologies as cost effective solutions of Stratospheric Communication Platforms (SCP) as future backbone of terrestrial networks for rural communications. The launch or putting in position the airship is not critical point such as launch of satellite and controlling support services in the creation of space-based communication technology and the most expensive phase of the total system cost. Therefore, with few cost effective remote controlled and solar powered airships can be covered some region or country including remote and rural areas with low density of population. The airship SCP network offers better solutions than cellular radio systems, with greater speed of transmission than even optical modes, roaming will be enhanced without severe shadowing or obstacle problems and disturbances inside of buildings and service will cost less. The SPS mission system is more autonomous and discrete, can be integrated with current satellite and cellular systems, and will be the best solution for rural, mobile transportation and military applications. The SCP airship can be seen well from all positions inside coverage area, because they are overlapping the total coverage and because of elevation angle. In any circumstances mountains, buildings and even trees cannot cause obstructions like to cellular network. For these reasons, there is currently a revival of interest for SCP constellations and application types of various system concepts are being studied.